Influence of ICRF-NBI synergy on fast ion distribution and plasma performance in second harmonic heating experiments with deuterium NBI at EAST. (1st May 2023) - Zhang, W.; Zhu, G.-H.; Zhang, X.-J.; Zhong, G.-Q.; Ai, L.; Chu, Y.-Q.; Fan, T.-S.; Fan, H.-C.; Guo, Y.-Y.; Hao, B.-L.; Huang, J.; Jin, Y.-F.; et al.
Abstract: Ion Cyclotron Range of Frequencies (ICRF) heating and Neutral Beam Injection (NBI) can have synergy due to the acceleration of NBI beam ions by ICRF wave fields at their harmonics. To understand the influence of ICRF-NBI synergy on fast ion distribution and plasma performance, dedicated experiments and TRANSP simulations have been carried out on EAST. The simulation results are consistent with the experimental results. They show that the ICRF-NBI synergy not only accelerates the NBI beam ions with energy lower than 80 keV to energy larger than 300 keV, but also generates fusion neutrons with energy larger than 3 MeV. Moreover, ICRF-NBI synergy improves the plasma performance by increasing the poloidal beta, plasma stored energy, core ion temperature, total neutron yield and kinetic pressure. In a typical H-mode plasma with 1.0 MW NBI and 1.5 MW ICRF power, it was observed that ICRF-NBI synergy increases the poloidal beta, plasma stored energy, core ion temperature and neutron yield by ∼35%, 33%, 22% and 80%, respectively. Various parameter scans show that the ICRF-NBI synergetic effects can be enhanced by decreasing the minority ion concentration or the distance between the harmonic resonance and magnetic axis, or by increasing the ICRF heating power or NBI beam energy. Consequently, this leads to a generation of fast ions with higher energy. For instance, the maximum energy of the fast ion tail increases from 300 to 600 keV as n(H) decreases from 5% to 0.1%.